Self-medication as a factor in treatment failure in patients treated for malaria with ACTs in a rural community of Enugu State, Southeast Nigeria - Umegbolu, Emmanuel I.; Ugwunna, Nwachukwu C.; Ikwuka, David C. (International Journal Of Community Medicine And Public Health, 2021)
Background: Self-medication (SM) is the taking of drugs, herbs or home remedies on one’s own initiative, or following the advice of another person, without consulting the doctor. Drugs that are prone to SM include analgesics, antibiotics, cough syrups, and antimalarials. Treatment failure (TF) in malaria is defined as the inability to clear malarial parasitaemia or resolve clinical symptoms despite administration of an antimalarial medicine. Among other factors, SM has been implicated as a cause of TF. The study aimed to determine the role of SM in TF observed in patients treated with artemisinin-based combination therapies (ACTs) and the strategies employed to tackle this problem. Methods: 172 patients diagnosed with malaria within the period of the study, were interviewed and 102 of them who engaged in SM with ACTs prior to presentation to the hospital were purposively selected. Data were collected over a period of one month (January 2021) and analysed as descriptive statistics of proportion. Results: Prevalence of SM among the patients diagnosed with malaria was 59%, and TF in those who engaged in SM 99%. 100% cure rate was recorded using modified triple ACT (TACT) and drug cycling with chloroquine tablets. Conclusions: The prevalence of SM was 59%, TF 99% and cure rate with modified TACT and drug cycling 100%. The drug regulatory body needs to ensure quality assurance of the ACTs used in the country, and in addition, promote patient education on the adverse effects of irrational SM.